Analisis Pendapatan Pedagang Koran Asongan di Kota Pekanbaru Provinsi Riau - Listihana, Wita Dwika; Aquino, Afvan (Jurnal Daya Saing, 2015)
Abstract: This Research is aimed to analyze causal factors of the school- age children choosing to work as street newspaper seller, how the pattern of work activity is done, and their participation to family prosperity. The method of this research used survey approach. The sample of this research amount of 40 respondent and used the purposive sampling technique. The research location is in Pekanbaru City, Riau Province with took the location in road intersection of traffic light. The type of data used the primary data by spreading questionnaires and the data analysis in this research used the descriptive-kualitatave. The result showed that factors that caused of school-age children choose to work as street newspaper seller consist of three factors. First, the reason for choosing the job, in this issue at most because of the own disires that is 80% respondents. Second, the reason for doing the job, at most to support family’s economic that is 60% respondents. Third, motivation become a street newspaper seller, at most to get the money that is 75% respondets. Furthermore, the pattern of work activity that is done by road news paper seller can show in three things that are the way of selling, the time of selling and kinds of news papers that is sold. First, the majority of street newspaper seller do the selling with take news papers in an agent or a coordinator that related to the owner’s of news paper that is 77,5% respondents. Second, the time of selling at most is in the morning until the day that is 42,5% respondent.Third, 82,5% respondent sell more than two kinds of news paper. Finally, Their participation into family prosperity is showed by amount of income and the using of income that is received. First, amount of income at most is the income under Rp 50.000,- that is 62,5% respondents. Second, the using of income at most is for school needs and to support their parents that is 37,5% respondents. Keywords: Income, Street newspaper seller, and School-age children